Generic convergence of infinite products of nonexpansive mappings with unbounded domains - Reich, Simeon; Zaslavski, Alexander J. (Frontiers in Applied Mathematics and Statistics, 2015)
We study the generic convergence of infinite products of nonexpansive mappings with unbounded domains in hyperbolic metric spaces.